Wells Cathedral
The three tall lancet windows of the west front, seen from the High Altar, integrate with the interior no less easily than with the front itself. The choir, which was the starting point of all the rebuilding, the transepts, the central tower, and the eastern bays of the nave were all completed up to roof level by the turn of the century, and employed the pointed arch exclusively. The nave was designed to be roofed with vaulting from the first, and Wells must be regarded as the prototype for Early English work at Lincoln.